2016
DOI: 10.3390/en9050374
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Analysis of Different Parts of Date Palm (Phoenix dactylifera L.) Using Ultimate, Proximate and Thermo-Gravimetric Techniques for Energy Production

Abstract: Abstract:The objective of the study was to analyze chemical structure of date palm (Phoenix dactylifera L.) by employing ultimate, proximate and thermo-gravimetric techniques. Samples from different anatomical parts of date palm, namely trunk, frond base, frond midrib, leaflets, coir, fruit stem, date stone, and fruit empty bunches were considered for the experiments. Based on the findings in this work palm leaflet samples gave the highest amount of extractives content (32.9%), followed by date palm stone spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
44
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(67 citation statements)
references
References 45 publications
13
44
1
2
Order By: Relevance
“…Biomass Corn stover 13 17.65 Walnut shell 13 20.18 Wheat straw 13 16.71 Cotton stalk 13 18 The calorific value of DPM samples were also verified with those from the work of Nasser et al, where the values were found to be in agreement with the reported figures 9 . The comparatively lower calorific values of DPF may be due to its low lignin content, as also revealed by Nasser et al in their work.…”
Section: Calorific Valuesupporting
confidence: 82%
See 3 more Smart Citations
“…Biomass Corn stover 13 17.65 Walnut shell 13 20.18 Wheat straw 13 16.71 Cotton stalk 13 18 The calorific value of DPM samples were also verified with those from the work of Nasser et al, where the values were found to be in agreement with the reported figures 9 . The comparatively lower calorific values of DPF may be due to its low lignin content, as also revealed by Nasser et al in their work.…”
Section: Calorific Valuesupporting
confidence: 82%
“…All samples were found to have lost half of their initial mass at around 320-340°C, where the 2nd stage active pyrolysis was ongoing, signifying that more than half of the tested DPF samples' mass was composed of hemicellulose and cellulose -the two most reactive natural polymeric fibers that break down at this particular thermal degradation stage. These findings were verified with the reported hemicellulose and cellulose content in Sukkari variety; hemicellulose content was reported to be between 43-45% by weight, and cellulose content was in the range of 28-31% by weight 9 . The high reactivity of DPF samples at low temperatures releasing high amount of volatiles revealed their potentials for pyrolysis and low temperature gasification purposes.…”
Section: Thermal Decomposition Stagessupporting
confidence: 77%
See 2 more Smart Citations
“…Their cellulose content was 40.99% and 39.00%, respectively, which is suitable for pulp and paper manufacturing (close to or above 40%) (Samariha and Khakifirooz 2011). However, millet stalks had a similar content of 39.4%, and date palm leaves have 39.37% as observed by Harinarayana et al (2005) and Nasser et al (2016), respectively. Compared to other non-woods, millet stalks and date palm leaves were higher than that of sorghum 35.87% (Cardoso et al 2013), corncob residues 38.8% (Liu et al 2010), rice husk 36%, and cotton stalk 38% (Singh and Chouhan 2014).…”
Section: Papers Surface Morphologysupporting
confidence: 58%